Negative electrode material for secondary battery, and secondary battery

By using silicon particles covered with phosphate compounds and hydrophobic polymer compounds in the negative electrode material of the secondary battery, the problem of degradation of cyclic characteristics in the secondary battery caused by side reactions is solved, and better cyclic performance is achieved.

CN119856295APending Publication Date: 2025-04-18PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380064636.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-29
Filing Date
2023-09-13
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

In secondary batteries, side reactions caused by contact between silicon-containing particles and electrolytes will lead to a decrease in circulation characteristics.

Method used

An anode material containing silicon particles and a cover layer covering its surface is used, which contains a phosphate compound and a hydrophobic polymer compound to inhibit side reactions.

Benefits of technology

The cycle characteristics of the secondary battery are effectively suppressed and the cycle performance of the battery is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119856295A_ABST
    Figure CN119856295A_ABST
Patent Text Reader

Abstract

This negative electrode material for a secondary battery is provided with silicon-containing particles and a coating layer that covers at least a part of the surface of the silicon-containing particles. The coating layer contains a phosphate compound and a hydrophobic polymer compound.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a negative electrode material for a secondary battery and a secondary battery. Background Art

[0002] Secondary batteries represented by lithium-ion secondary batteries are used as power sources for electronic devices such as portable terminals, power sources for vehicles such as electric vehicles, etc. The negative electrode of the secondary battery uses a negative electrode active material that can absorb and release lithium ions, and graphite is generally used as such a negative electrode active material.

[0003] In recent years, silicon-containing materials having a higher capacity density than graphite have been studied as negative electrode active materials.

[0004] Patent document 1 proposes a negative electrode active material for a secondary battery, which comprises: a silicate phase containing Li, Si and Mx (Mx is an alkali metal, an alkaline earth metal, and an element other than Si); silicon particles dispersed in the aforementioned silicate phase; and metal particles with one or more metals or alloys selected from Fe, Cr, Ni, Mn, Cu, Mo, Zn, and Al as the main component dispersed in the aforementioned silicate phase, wherein the content of each element is 3 to 45 mol% for Li, 40 to 78 mol% for Si, and 1 to 40 mol% for Mx relative to the total amount of elements other than oxygen in the aforementioned silicate phase.

[0005] Patent document 2 proposes a negative electrode active material for a secondary battery, which comprises: a silicate phase containing Li, Si and Mx (Mx is an alkali metal, an alkaline earth metal, and an element other than Si); silicon particles dispersed in the aforementioned silicate phase; and oxide particles dispersed in the aforementioned silicate phase (the oxide particles include: at least any one of oxide particles containing Zr, oxide particles containing Ce, oxide particles containing Ca, oxide particles containing Al, oxide particles containing Fe, oxide particles containing Mg, oxide particles containing Ti and oxide particles containing W), wherein the content of each element relative to the total of elements other than oxygen in the aforementioned silicate phase is 3 to 45 mol% for Li, 40 to 78 mol% for Si, and 1 to 40 mol% for Mx.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: International Publication No. 2019 / 151016 Pamphlet

[0009] Patent Document 2: International Publication No. 2019 / 151026 Pamphlet Summary of the invention

[0010] Problem that the invention aims to solve

[0011] In secondary batteries, side reactions due to contact of silicon-containing particles with an electrolyte may lead to a decrease in cycle characteristics.

[0012] Solutions for solving problems

[0013] In view of the above, one aspect of the present disclosure is directed to a negative electrode material for a secondary battery, comprising silicon-containing particles and a covering layer covering at least a portion of the surface of the silicon-containing particles, wherein the covering layer contains a phosphate compound and a hydrophobic polymer compound.

[0014] Another aspect of the present disclosure relates to a negative electrode material for a secondary battery, comprising silicon-containing particles and a covering layer covering at least a portion of a surface of the silicon-containing particles, wherein the covering layer contains a phosphate compound and a water-insoluble polymer compound.

[0015] Still another aspect of the present disclosure relates to a secondary battery including a positive electrode, a negative electrode, and an electrolyte, wherein the negative electrode includes the negative electrode material for a secondary battery.

[0016] Effects of the Invention

[0017] According to the present disclosure, it is possible to suppress a decrease in the cycle characteristics of a secondary battery.

[0018] The novel features of the present invention are set forth in the appended claims, but both the configuration and content of the present invention, together with other objects and features of the present invention, will be more fully understood from the following detailed description with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 It is a cross-sectional view schematically showing a negative electrode material for a secondary battery according to one embodiment of the present disclosure.

[0020] Figure 2 This is a schematic perspective view in which a portion of a secondary battery according to an embodiment of the present disclosure is cut away. DETAILED DESCRIPTION

[0021] Hereinafter, examples are given to illustrate the embodiments of the present disclosure, but the present disclosure is not limited to the examples described below. In the following description, specific numerical values ​​and materials are sometimes exemplified, but other numerical values ​​and materials may also be applied as long as the effects of the present disclosure can be obtained. In this specification, the so-called "numerical value A to numerical value B" includes numerical value A and numerical value B, and can be read alternatively as "above numerical value A and below numerical value B". In the following description, when the lower limit and upper limit of numerical values ​​involving specific physical properties, conditions, etc. are exemplified, as long as the lower limit is not higher than the upper limit, any one of the exemplified lower limits and any one of the exemplified upper limits may be arbitrarily combined. When multiple materials are exemplified, one may be selected and used alone, or two or more may be used in combination.

[0022] In addition, the present disclosure includes a combination of matters described in two or more claims arbitrarily selected from a plurality of claims in the appended claims. That is, matters described in two or more claims arbitrarily selected from a plurality of claims in the appended claims may be combined as long as no technical contradiction occurs.

[0023] (Negative electrode materials for secondary batteries)

[0024] A secondary battery negative electrode material according to one embodiment of the present disclosure includes silicon-containing particles (Si-based active material) and a covering layer covering at least a portion of the surface of the silicon-containing particles. The covering layer contains a phosphate compound and a hydrophobic polymer compound.

[0025] From the viewpoint of improving cycle characteristics and increasing capacity, the silicon-containing particles are preferably composite particles comprising an ion-conducting phase and a silicon phase dispersed in the ion-conducting phase. The ion-conducting phase may, for example, comprise at least one selected from the group consisting of a silicate phase, a silicon oxide phase, and a carbon phase. Hereinafter, at least one of the silicate phase and the silicon oxide phase is also referred to as a "silicon compound phase". Composite particles in which a silicon phase is dispersed in a silicate phase are also referred to as "composite particles containing a silicate phase". Composite particles in which a silicon phase is dispersed in a silicon oxide phase are also referred to as "composite particles containing a silicon oxide phase". Composite particles in which a silicon phase is dispersed in a carbon phase are also referred to as "composite particles containing a carbon phase".

[0026] By covering the surface of the silicon-containing particles with the phosphate compound, the silicon-containing particles are protected by the electrolyte, and a side reaction with the electrolyte is suppressed, thereby suppressing a decrease in cycle characteristics due to the side reaction.

[0027] However, conventionally, the retention of phosphate compounds on the surface of silicon-containing particles is insufficient. In addition, the phosphate compounds on the surface of silicon-containing particles are easily dissolved in water when preparing negative electrode slurry, and the effect of the phosphate compounds cannot be fully obtained, leaving room for improvement in cycle characteristics.

[0028] In contrast, in the present disclosure, the covering layer includes a phosphate compound and a hydrophobic polymer. As a result, the retention of the phosphate compound on the surface of the silicon-containing particles is improved, and the surface of the silicon-containing particles is effectively covered with the phosphate compound. As a result, the effect of protecting the silicon-containing particles brought by the phosphate compound can be significantly obtained (in the case of composite particles, the effect of inhibiting ion conduction phase corrosion). As a result, the cycle characteristics can be greatly improved.

[0029] The negative electrode is prepared, for example, by preparing a slurry containing a negative electrode material and water, applying the slurry to a negative electrode collector, drying, and rolling as needed to form a negative electrode mixture layer to prepare a negative electrode. By forming a hydrophobic polymer compound on the surface of the negative electrode material, the dissolution of the phosphate compound into water is suppressed when preparing a slurry containing water. The hydrophobic polymer compound is expected to be a material having both excellent adhesion and hydrophobicity.

[0030] A certain degree of phosphate compound and hydrophobic polymer compound may be mixed in the covering layer. The covering layer may be composed of a layer of phosphate compound and a layer of hydrophobic polymer compound formed on the layer of phosphate compound. From the viewpoint of easily improving the retention of phosphate compound, the content of hydrophobic polymer compound in the surface layer of the covering layer may be greater than that in the inner layer of the covering layer. It should be noted that the surface layer of the covering layer refers to a region where the distance from the outermost surface of the covering layer is less than 1 / 2 of the thickness of the covering layer. The inner layer of the covering layer refers to a region where the distance from the outermost surface of the covering layer is greater than 1 / 2 of the thickness of the covering layer.

[0031] (Phosphate compounds)

[0032] The coating layer containing the phosphate compound has low resistance and good ion conductivity. The phosphate compound can form a P(=O)O - The anions and cations of the structure (also called "PO structure") include metal ions, ammonium ions (NH4 + )wait.

[0033] In the PO structure, the combination of P and O can be a single bond (PO), a double bond (P=O), or a bond in between. The PO structure can also form a PO3 structure. The PO3 structure can be included in, for example, PO3 3- 、HPO3 2- 、H2PO3 - In the case where the covering layer contains a phosphate compound, a peak derived from a PO structure (or a PO3 structure) can be observed by X-ray photoelectron spectroscopy (XPS).

[0034] Examples of metals that can form cations in phosphate compounds include alkali metals, beryllium, magnesium, alkaline earth metals, transition metals, and aluminum. Examples of alkali metals include sodium and potassium. Examples of alkaline earth metals include calcium. Examples of transition metals include iron, manganese, and nickel. The phosphate compound may be an inorganic phosphate compound or an organic phosphate compound.

[0035] The phosphate compound preferably contains at least one selected from the group consisting of phosphate compounds containing an anion represented by the general formula (1), polyphosphate compounds, and metaphosphate compounds.

[0036]

[0037] In the general formula (1), A is an organic group or an oxygen atom. In the case of an organic group, for example, two phosphorus atoms in the anion represented by the general formula (1) are bonded via a carbon atom.

[0038] In the case of a phosphate compound containing an anion represented by the general formula (1), the cycle characteristics tend to be significantly improved. The detailed reason is not clear, but it is presumed as follows.

[0039] The phosphate compound contains anions having a plurality of PO structures. Such a phosphate compound can react with a decomposition product of an electrolyte (e.g., HF) to form a soft polymer on the surface or inside of the covering layer. The covering layer containing such a polymer can easily follow the expansion and contraction of the silicon-containing particles, and the protective effect of the covering layer on the silicon-containing particles can be maintained more firmly during the charge and discharge cycle. In addition, the isolation of particles caused by particle rupture can also be suppressed. In addition, the covering layer containing the polymer has low resistance and good ion conductivity.

[0040] The phosphate compound has a plurality of PO structures, has good affinity with water, and is excellent in dispersibility in water. In the wet mixing process of the first step of the negative electrode material preparation method described later, the phosphate compound is dispersed in water and mixed with silicon-containing particles in this state, so that the surface of the silicon-containing particles is easily uniformly covered with the phosphate compound, and the coverage of the phosphate compound is improved.

[0041] The covering layer may contain at least one of the following phosphate compounds: a phosphate compound containing one anion and cation represented by the general formula (1); and a phosphate compound containing another anion and cation represented by the general formula (1).

[0042] A in the general formula (1) is an organic group, and the organic group preferably has a structure represented by the formula (2).

[0043]

[0044] In this case, the phosphate compound containing the anion represented by the general formula (1) is etidronate. Examples of etidronate include disodium etidronate (C2H6Na2O7P2) and tetrasodium etidronate (C2H4Na4O7P2).

[0045] Examples of the phosphate compound containing an anion represented by the general formula (1) wherein A in the general formula (1) is an organic group include, in addition to etidronate, clodronate, tedronate, and the like.

[0046] A phosphate compound containing an anion represented by the general formula (1) wherein A in the general formula (1) is an oxygen atom is a pyrophosphate. Examples of pyrophosphates include sodium pyrophosphate (Na4P2O7), potassium pyrophosphate (K4P2O7), calcium pyrophosphate (Ca2P2O7), and iron pyrophosphate (Fe4(P2O7)3).

[0047] The polyphosphate compound includes, for example, at least one selected from the group consisting of tripolyphosphate and tetrapolyphosphate. Examples of tripolyphosphate include sodium tripolyphosphate (Na5P3O 10 ) etc. As tetrapolyphosphate, for example, sodium tetrapolyphosphate (Na6P4O 13 )wait.

[0048] The metaphosphate compound includes, for example, at least one selected from the group consisting of trimetaphosphate and hexametaphosphate. As trimetaphosphate, sodium trimetaphosphate ((NaPO3)3), potassium trimetaphosphate ((KPO3)3), etc. can be listed. As hexametaphosphate, for example, sodium hexametaphosphate ((NaPO3)6), potassium hexametaphosphate ((KPO3)6), etc. can be listed.

[0049] Among them, the phosphate compound is preferably etidronate from the viewpoint that a soft polymer derived from a phosphate compound is easily formed in the covering layer, and the protective effect of the covering layer on the silicon-containing particles is more firmly maintained during the charge and discharge cycle. Etidronate has many hydroxyl groups and has good affinity with water, and is also preferred from the viewpoint that the dispersibility in water is further improved.

[0050] In addition, as the phosphate compound, PO4 3- 、HPO4 2- or H2PO4 - Salts of inorganic phosphoric acid containing anions and cations. Examples of such phosphate compounds include sodium dihydrogen phosphate, disodium hydrogen phosphate, trisodium phosphate, potassium dihydrogen phosphate, dipotassium hydrogen phosphate, tripotassium phosphate, trilithium phosphate, LiH2PO4, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, triammonium phosphate, calcium dihydrogen phosphate, dicalcium hydrogen phosphate, tricalcium phosphate, magnesium dihydrogen phosphate, dimagnesium hydrogen phosphate, trimagnesium phosphate, aluminum dihydrogen phosphate, aluminum dihydrogen phosphate, trialuminum phosphate, manganese dihydrogen phosphate, zinc phosphate, boron phosphate, and the like.

[0051] The amount of phosphate compound covering the surface of the silicon-containing particles (hereinafter also referred to as the loading amount of the phosphate compound) can be 1 part by mass or more (or 2 parts by mass) relative to 100 parts by mass of the silicon-containing particles, can be 1 part by mass or more and 10 parts by mass or less, or can be 5 parts by mass or more and 10 parts by mass or less.

[0052] When the loading amount of the phosphate compound is more than 1 part by mass, the surface of the silicon-containing particles can be fully covered with the phosphate compound, and the side reaction inhibition effect brought by the phosphate compound can be easily obtained. When the loading amount of the phosphate compound is more than 1 part by mass and less than 10 parts by mass, the larger the loading amount, the easier it is to improve the cycle characteristics. When the loading amount of the phosphate compound is less than 10 parts by mass, it is easy to obtain a negative electrode material (covering layer) with low resistance.

[0053] The thickness of the covering layer is preferably so thin that it does not substantially affect the average particle size of the silicon-containing particles. From the viewpoint of protecting the silicon-containing particles from the influence of the electrolyte, the thickness of the covering layer is preferably 1 nm or more. From the viewpoint of suppressing the increase in resistance, the thickness of the covering layer is preferably 300 nm or less. The thickness of the covering layer may be less than the thickness of the conductive layer described later. The thickness of the covering layer can be measured by cross-sectional observation of the silicon-containing particles using an electron microscope. The electron microscope uses a scanning electron microscope (SEM) or a TEM (transmission electron microscope).

[0054] The phosphate compound contained in the coating layer of the negative electrode material can be confirmed by, for example, using time-of-flight secondary ion mass spectrometry (TOF-SIMS). In the coating layer, ions derived from the phosphate compound can be detected.

[0055] (Hydrophobic polymer compound)

[0056] The hydrophobic polymer compound is expected to have good adhesiveness and hot melt properties. In this case, the phosphate compound can be firmly supported on the surface of the silicon-containing particles by the hydrophobic polymer compound, and the effect of inhibiting side reactions brought by the phosphate compound can be easily and stably obtained. The hydrophobic polymer compound is almost insoluble in water.

[0057] From the viewpoint of stability to the electrolyte, the hydrophobic polymer compound preferably includes a fluororesin. The fluororesin preferably includes at least one selected from the group consisting of polyvinylidene fluoride (PVDF), polytetrafluoroethylene, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, tetrafluoroethylene-ethylene copolymer, trifluorochloroethylene-ethylene copolymer and polytrifluorochloroethylene. Among them, PVDF is more preferred. In the case of PVDF, it has good adhesion, low melting point, and can form a covering layer at a low heat treatment temperature.

[0058] The hydrophobic polymer compound can include a polymer containing a vinylidene fluoride unit in addition to polyvinylidene fluoride. The example of the polymer containing the vinylidene fluoride unit includes a copolymer of vinylidene fluoride and other monomers. The example of other monomers includes hexafluoropropylene (HFP) and tetrafluoroethylene (TFE). As the macromolecule containing the vinylidene fluoride unit, polyvinylidene fluoride and its modified substance, vinylidene fluoride-hexafluoropropylene copolymer, vinylidene fluoride-chlorotrifluoroethylene copolymer etc. can be listed. In the macromolecule containing the vinylidene fluoride unit, the content of the vinylidene fluoride unit is, for example, more than 30 mol %, and can be more than 50 mol %.

[0059] The amount of the hydrophobic polymer compound covering the surface of the silicon-containing particles (hereinafter also referred to as the loading amount of the hydrophobic polymer compound) can be more than 1 mass part (or more than 2 mass parts) relative to 100 mass parts of the silicon-containing particles, can be more than 1 mass part and less than 10 mass parts, can be more than 1 mass part and less than 6 mass parts, or can be more than 2 mass parts and less than 6 mass parts.

[0060] When the loading amount of the hydrophobic polymer compound is 1 part by mass or more, the effect of improving the retention of the phosphate compound on the surface of the silicon-containing particles brought by the hydrophobic polymer compound can be fully obtained. When the loading amount of the hydrophobic polymer compound is 6 parts by mass or less, it is easy to obtain a negative electrode material (covering layer) with low resistance.

[0061] When the covering layer contains a phosphate compound and a fluororesin (for example, PVDF), the supported amounts of the phosphate compound and the fluororesin (the amounts relative to 100 parts by mass of the silicon-containing particles) can be determined by the following method.

[0062] The negative electrode material is washed with N-methyl-2-pyrrolidone (NMP) to dissolve the fluororesin, and the difference in the mass of NMP before and after dissolution is calculated as the mass of the fluororesin. Then, the residue insoluble in NMP is washed with water to dissolve the phosphate compound. The mass of the phosphate compound dissolved in water is calculated by quantitative analysis such as inductively coupled plasma (ICP) emission spectrometry.

[0063] When the negative electrode material comprises composite particles containing a silicon compound phase (or particles of silicon single substance or silicon alloy), the mass of the residue insoluble in water and NMP is determined as the mass of the composite particles containing a silicon compound phase (or particles of silicon single substance or silicon alloy).

[0064] When the negative electrode material has composite particles of a silicon-containing compound phase having a conductive layer, the residue insoluble in water and NMP is subjected to quantitative analysis of carbon using a carbon sulfur analyzer or the like. The amount of carbon obtained is derived from the carbon material of the conductive layer. The mass of the composite particles containing the silicon-containing compound phase is obtained by subtracting the mass of the carbon obtained by analysis from the mass of the residue insoluble in water and NMP.

[0065] The supported amount of the fluororesin is determined by (mass of the fluororesin / mass of the silicon-containing particles)×100 using the mass of the fluororesin and the mass of the silicon-containing particles determined above.

[0066] The supported amount of the phosphate compound is determined by (mass of the phosphate compound / mass of the silicon-containing particles)×100 using the mass of the phosphate compound and the mass of the silicon-containing particles determined above.

[0067] The thickness of the covering layer is preferably so thin that it does not substantially affect the average particle size of the silicon-containing particles. From the viewpoint of protecting the silicon-containing particles from the influence of the electrolyte, the thickness of the covering layer is preferably 1 nm or more. From the viewpoint of suppressing the increase in resistance, the thickness of the covering layer is preferably 300 nm or less. The thickness of the covering layer may be less than the thickness of the conductive layer described later. The thickness of the covering layer can be measured by observing the cross section of the silicon-containing particles using an electron microscope. The electron microscope uses a scanning electron microscope (SEM) or a TEM (transmission electron microscope).

[0068] (Conductive layer)

[0069] In the case where the silicon-containing particles are composite particles, the electrical conductivity may be relatively low depending on the composition of the ion-conducting phase. From the viewpoint of improving electrical conductivity, a conductive layer comprising a conductive carbon material may be sandwiched between the composite particles and the covering layer. That is, the covering layer may be formed in the form of a conductive layer covering the surface of the composite particles. The thickness of the conductive layer is preferably substantially thin to such an extent that the average particle size of the composite particles is not affected. From the viewpoint of ensuring electrical conductivity, the thickness of the conductive layer is preferably more than 1 nm. From the viewpoint of suppressing the increase in resistance, the total thickness of the covering layer and the conductive layer is preferably less than 300 nm. The thickness of the conductive layer can be measured in the same manner as in the case of the covering layer.

[0070] The conductive layer is formed by mixing the raw material of the conductive carbon material with the composite particles, firing the mixture, and carbonizing the raw material of the conductive carbon material. As the raw material of the conductive material, for example, coal tar or coal tar tar, petroleum asphalt, phenolic resin, etc. can be used. The mixture of the raw material of the conductive carbon material and the composite particles is fired, for example, in an inert atmosphere (for example, an atmosphere of argon, nitrogen, etc.). The firing temperature is preferably above 450°C and below 1000°C. If within the above temperature range, it is easy to form a conductive layer with high conductivity in the silicate phase with low crystallinity. The firing temperature is preferably above 550°C and below 900°C, and more preferably above 650°C and below 850°C. The firing time is, for example, above 1 hour and below 10 hours.

[0071] (Method for producing negative electrode material for secondary battery)

[0072] The method for producing a negative electrode material for a secondary battery (a method for forming a covering layer) includes, for example, the following first to third steps.

[0073] Step 1: Wet-mixing and drying of the phosphate compound and silicon-containing particles. In this way, a first intermediate (silicon-containing particles with the phosphate compound attached to the surface) is obtained.

[0074] Step 2: Dry-mixing the first intermediate and the hydrophobic polymer compound. In this way, a second intermediate (silicon-containing particles having a phosphate compound and a hydrophobic polymer compound attached to the surface) is obtained.

[0075] Step 3: Heat-treating the second intermediate in an inert atmosphere. In this way, a coating layer containing a phosphate compound and a hydrophobic polymer compound is formed on the surface of the silicon-containing particles.

[0076] The first step and the second step may be performed in the air, but are preferably performed in an inert atmosphere.

[0077] (1st step)

[0078] In the wet mixing in the first step, the phosphate compound and the solvent (dispersion medium) may be mixed, and then the solution (dispersion liquid) of the phosphate compound and the silicon-containing particles may be mixed.

[0079] As the solvent (dispersion medium), water, alcohol, etc. can be used, and water is preferred. In this case, the surface of the silicon-containing particles can be easily and uniformly covered with the phosphate compound.

[0080] The amount of the phosphate compound added in the first step may be 1 part by mass or more (or 2 parts by mass or more) and 10 parts by mass or less relative to 100 parts by mass of the silicon-containing particles.

[0081] (Second step)

[0082] The dry mixing can be performed using a ball mill. The amount of the hydrophobic polymer compound added in the second step can be 1 part by mass or more (or 2 parts by mass or more) and 6 parts by mass or less relative to 100 parts by mass of the silicon-containing particles.

[0083] (Step 3)

[0084] In the heat treatment process, the second intermediate is heated to a temperature above the melting point of the hydrophobic polymer compound, for example. Through the heat treatment process, the hydrophobic polymer compound is liquefied, and the gap between the silicon-containing particles and the particles of the phosphate compound and the gap between the particles of the phosphate compound are filled, and the surrounding of the particles of the silicon-containing particles and the phosphate compound is infiltrated and diffused. Thus, the retention of the phosphate compound on the surface of the silicon-containing particles is greatly improved. By crushing the obtained by heat treating the second intermediate, the silicon-containing particles with a coating layer are obtained. In the case where the silicon-containing particles are composite particles with a conductive layer on the surface, a coating layer can also be formed on the surface of the silicon-containing particles across the conductive layer.

[0085] Heat treatment is preferably carried out at a temperature above the melting point of the hydrophobic polymer compound and below the decomposition temperature of the hydrophobic polymer compound. When polyvinylidene fluoride (PVDF) is used as the hydrophobic polymer compound, the heat treatment temperature is above the melting point (150°C to 170°C) of PVDF and below the decomposition temperature (340°C), preferably, for example, 200°C to 250°C. Heat treatment is carried out under an inert gas atmosphere. The heat treatment time is, for example, about 1 to 3 hours.

[0086] By the above-mentioned method for preparing the negative electrode material, it is easy to form a covering layer in which the content of the hydrophobic polymer compound in the surface layer of the covering layer is greater than that in the inner layer of the covering layer. It should be noted that the composition analysis in the depth direction of the covering layer can be performed using X-ray photoelectron spectroscopy (XPS), time-of-flight secondary ion mass spectrometry (TOF-SIMS), etc.

[0087] The particle sizes of the phosphate compound added in the first step and the hydrophobic polymer compound added in the second step are preferably smaller than the particle size of the silicon-containing particles. In this case, the surface of the silicon-containing particles (covering layer) can be easily and uniformly covered with the phosphate compound and the hydrophobic polymer compound. The average particle sizes of the phosphate compound and the hydrophobic polymer compound can be 1 to 100 μm, or 1 to 10 μm, respectively.

[0088] A secondary battery negative electrode material according to another embodiment of the present disclosure includes silicon-containing particles and a covering layer covering at least a portion of the surface of the silicon-containing particles. The covering layer contains a phosphate compound and a water-insoluble polymer compound.

[0089] In the case of a covering layer comprising a phosphate compound and a water-insoluble polymer compound, the same effect as that of a covering layer comprising a phosphate compound and a hydrophobic polymer compound can be obtained. By covering the surface of the silicon-containing particles with a covering layer comprising a phosphate compound and a water-insoluble polymer compound, side reactions are suppressed, and the reduction in cycle characteristics caused by side reactions is suppressed.

[0090] (Water-insoluble polymer compound)

[0091] The water-insoluble polymer compound refers to a polymer compound in which less than 0.02 g (or less than 0.01 g) is dissolved when 1 g of the polymer compound is added to 100 g of water at 25° C. and the water is stirred sufficiently.

[0092] Examples of the water-insoluble polymer compound include hydrophobic polymer compounds (such as fluororesins) and polymethyl methacrylate, polyethylene terephthalate, polybutylene terephthalate, polyacrylonitrile, polyimide, polyamide, polyethylene, polypropylene, polystyrene, polyvinyl chloride, and polycarbonate.

[0093] (Composite particles)

[0094] In the case where the silicon-containing particles are composite particles, the surfaces of the composite particles (ion-conducting phase) are covered with a phosphate compound and a hydrophobic polymer compound, thereby protecting the composite particles from the influence of the electrolyte, suppressing side reactions with the electrolyte, and suppressing corrosion of the ion-conducting phase accompanying the side reactions. The reduction in cycle characteristics due to deterioration of the composite particles caused by the corrosion is suppressed.

[0095] The composite particles have a structure in which a silicon phase is dispersed in an ion-conducting phase (matrix). The stress accompanying the expansion and contraction of the silicon phase during charge and discharge is alleviated by the ion-conducting phase, and the cracking and breaking of the composite particles are suppressed. Therefore, it is possible to take into account both the high capacity brought about by the silicon content and the improvement of the cycle characteristics. The ion-conducting phase may include a silicon compound phase (at least one of a silicate phase and a silicon oxide phase), and may also include a carbon phase. The ion-conducting phase may be composed of one phase or a plurality of phases.

[0096] The silicon oxide phase is composed of a compound of Si and O. The main component of the silicon oxide phase (for example, 95 to 100% by mass) can be silicon dioxide. The silicate phase is composed of a compound containing a metal element, silicon (Si) and oxygen (O). The silicate phase preferably contains at least lithium silicate. In this case, lithium ions can more easily enter and exit the silicate phase. It should be noted that among the silicon oxide phase and the silicate phase, the silicate phase is preferably used as the main component from the aspect of small irreversible capacity. Here, "main component" refers to a component that accounts for more than 50% by mass of the total mass of the silicon compound phase, and may also account for more than 70% by mass. The ion-conducting phase is composed of a silicon compound phase, and contains a lithium silicate phase as a main component, and may also contain a small amount of silicon oxide phase.

[0097] The composite particles may be composite particles including a silicate phase and a silicon phase dispersed in the silicate phase (composite particles containing a silicate phase). Composite particles containing a silicate phase may be obtained, for example, by pulverizing a mixture of silicate and raw silicon while stirring it with a ball mill or the like, micronizing the mixture, heat-treating the mixture in an inert atmosphere, and pulverizing a sintered product obtained by the heat treatment.

[0098] The silicate phase preferably contains at least one of an alkali metal element (a Group 1 element other than hydrogen in the long period periodic table) and a Group 2 element in the long period periodic table. Alkali metal elements include lithium (Li), potassium (K), sodium (Na), etc. Group 2 elements include magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), etc. The silicate phase may further contain rare earth elements such as lanthanum (La), aluminum (Al), boron (B), and other elements.

[0099] Lithium silicate is a silicate containing lithium (Li), silicon (Si) and oxygen (O). The atomic ratio of O to Si in lithium silicate: O / Si is, for example, greater than 2 and less than 4 (z in the formula described below is 0<z<2). When the O / Si ratio is greater than 2 and less than 4, it is advantageous in terms of the stability of the silicate phase and lithium ion conductivity. Preferably, the O / Si ratio is greater than 2 and less than 3. The atomic ratio of Li to Si in lithium silicate: Li / Si is, for example, greater than 0 and less than 4.

[0100] The composition of lithium silicate can be expressed by the formula: Li 2z SiO 2+z (0<z<2). From the viewpoint of stability, ease of production, lithium ion conductivity, etc., 0<z≤1 can be adopted. Examples of lithium silicate include Li2Si2O5 (z=1 / 2) and Li2SiO3 (z=1).

[0101] The average particle size of the fine silicon phase (before the first charge) dispersed in the silicate phase can be less than 500nm, more than 200nm, or less than 50nm. By appropriately miniaturizing the silicon phase in this way, the volume change during charge and discharge becomes smaller, and the structural stability is improved. In addition, the cycle characteristics are improved by making the expansion and contraction of the silicon phase uniform and suppressing particle breakage. The average particle size of the silicon phase is determined by observing the cross section of the negative electrode material using SEM or TEM. Specifically, the maximum diameters of any 100 silicon phases are averaged and calculated.

[0102] The silicon phase dispersed in the silicate phase is a granular phase of silicon (Si) single substance and is composed of a single or multiple crystallites. The crystallite size of the silicon phase can be greater than 5nm and less than 50nm. When the crystallite size of the silicon phase is less than 50nm, the volume change caused by the expansion and contraction of the silicon particles during charging and discharging can be reduced, further improving the cycle characteristics. The crystallite size of the silicon phase can be calculated according to the Scherrer formula from the half-value width of the diffraction peak attributable to the Si (111) plane of the X-ray diffraction (XRD) pattern.

[0103] From the viewpoint of increasing capacity and improving cycle characteristics, the content of the silicon phase in the composite particles containing the silicate phase may be 30% by mass or more and 90% by mass or less, or 35% by mass or more and 75% by mass or less.

[0104] The composition of the composite particles containing a silicate phase can be determined, for example, by the following analysis method.

[0105] <EDX>

[0106] Randomly select 10 composite particles with a maximum diameter of 5 μm or more from the cross-sectional image of the reflected electron image of the negative electrode mixture layer, and perform element mapping analysis based on energy dispersive X-ray (EDX) on each composite particle. Use image analysis software to calculate the area ratio of the element being the object. The observation magnification is expected to be 2000 to 20000 times. Average the measured values ​​of the area ratio of the specified elements contained in the 10 particles. Calculate the content of the element being the object from the obtained average value.

[0107] Desirable measurement conditions for cross-sectional SEM-EDX analysis are shown below.

[0108] <SEM-EDX measurement conditions>

[0109] Processing equipment: JEOL, SM-09010 (Cross Section Polisher)

[0110] Processing conditions: Acceleration voltage 6kV

[0111] Current value: 140μA

[0112] Vacuum degree: 1×10 -3 ~2×10 -3 Pa

[0113] Measuring device: Electron microscope SU-70 manufactured by HITACHI

[0114] Accelerating voltage during analysis: 10kV

[0115] Field: Free Mode

[0116] Probe current mode: Medium

[0117] Probe Current Range: High

[0118] Anode Ap.: 3

[0119] OBJ Ap.:2

[0120] Analysis area: 1μm square

[0121] Analysis software: EDAX Genesis

[0122] CPS: 20500

[0123] Lsec: 50

[0124] Time constant: 3.2

[0125] <AES>

[0126] Randomly select composite particles with a maximum particle diameter of 5 μm or more from the cross-sectional image of the reflected electron image of the negative electrode mixture layer, and use an Auger electron spectroscopy (AES) analyzer (e.g., JAMP-9510F, manufactured by JEOL Ltd.) to perform qualitative and quantitative analysis of the elements on each composite particle. The measurement conditions can be, for example, an acceleration voltage of 10 kV, a beam current of 10 nA, and an analysis area of ​​20 μmφ. The content of the specified element contained in 10 particles is averaged to calculate the content.

[0127] It should be noted that during the charge and discharge process, a coating is formed on the surface of the composite particles due to electrolyte decomposition, etc. In addition, as described below, the composite particles sometimes also have a conductive layer covering the surface of the composite particles. Therefore, the mapping analysis based on EDX or AES is performed in a manner to avoid including a thin coating or a conductive layer within the measurement range, and is performed for a range of 1 μm inward from the peripheral edge of the cross section of the composite particles. Through mapping analysis, the distribution state of the carbon material inside the composite particles can also be confirmed. Since it is difficult to determine the decomposition products of the electrolyte at the end of the cycle, the measurement is preferably performed on samples before or at the beginning of the cycle.

[0128] <ICP>

[0129] The composite particle sample is completely dissolved in a heated acid solution (a mixture of hydrofluoric acid, nitric acid, and sulfuric acid), and the carbon in the solution residue is filtered and removed. The filtrate obtained is then analyzed by inductively coupled plasma emission spectrometry (ICP) to measure the spectral intensity of each element. Next, a calibration curve is prepared using a commercially available standard solution of the element to calculate the content of each element contained in the composite particle.

[0130] The contents of B, Na, K, and Al contained in the silicate phase can be quantitatively analyzed in accordance with JIS R3105 (1995) (Analysis method of borosilicate glass).

[0131] In the composite particles containing a silicate phase, there are a silicate phase and a silicon phase, which can be distinguished and quantified by using Si-NMR. The Si content obtained by the above method is the sum of the amount of Si constituting the silicon phase and the amount of Si in the silicate phase. The amount of Si element contained in the composite particles is distributed in the silicate phase and the silicon phase using the results of the quantitative analysis based on Si-NMR. It should be noted that the standard substance required for quantification can be a mixture of a silicate phase and a silicon phase containing a known Si content in a specified ratio.

[0132] Desirable Si-NMR measurement conditions are shown below.

[0133] <Si-NMR measurement conditions>

[0134] Measuring device: Varian, solid-state nuclear magnetic resonance spectrometer (INOVA-400)

[0135] Probe: Varian 7mm CPMAS-2

[0136] MAS: 4.2kHz

[0137] MAS speed: 4kHz

[0138] Pulse: DD (45° pulse + signal acquisition time 1H decoupling)

[0139] Repeat time: 1200sec~3000sec

[0140] Observation width: 100kHz

[0141] Observation center: around -100ppm

[0142] Signal acquisition time: 0.05 seconds

[0143] Total times: 560

[0144] Sample volume: 207.6 mg

[0145] Hereinafter, an example of a method for producing composite particles containing a silicate phase will be described in detail.

[0146] Step (i) (Step of Obtaining Lithium Silicate)

[0147] The raw material of lithium silicate uses a raw material mixture containing a Si-containing raw material and a Li raw material in a specified ratio. Other elements M may also be included in the raw material mixture as needed. The mixture obtained by mixing the above raw materials in specified amounts is dissolved, and the molten metal is passed through a metal roller to form a thin film to produce lithium silicate. Then, the thin-film silicate is heat-treated in an atmospheric atmosphere at a temperature above the glass transition point and below the melting point to crystallize it. It should be noted that the thin-film silicate can also be used without crystallization. In addition, it is also feasible to manufacture silicate by solid phase reaction instead of dissolving the mixture obtained by mixing in specified amounts and sintering it at a temperature below the melting point.

[0148] Silicon oxide can be used as Si raw material. For example, lithium carbonate, lithium oxide, lithium hydroxide, lithium hydride, etc. can be used as Li raw material. These can be used alone or in combination of two or more. The raw material of element M can include oxides, hydroxides, carbonate compounds, hydrides, nitrates, sulfates, etc. of each element.

[0149] The Si raw material that has not reacted with the Li raw material may remain in the lithium silicate. The remaining Si raw material is dispersed in the lithium silicate in the form of fine crystals of silicon oxide.

[0150] Step (ii) (Step of Obtaining Silicate Composite Particles)

[0151] Next, raw material silicon is mixed with lithium silicate to form a composite. For example, composite particles are produced through the following steps (a) to (c).

[0152] Process (a)

[0153] First, raw silicon powder and lithium silicate powder are mixed at a mass ratio of, for example, 20:80 to 95:5. Coarse silicon particles having an average particle size of about several μm to several tens of μm may be used as the raw silicon.

[0154] Process (b)

[0155] Next, a pulverizing device such as a ball mill is used to pulverize and compound the mixture of raw silicon and lithium silicate while micronizing the mixture. At this time, an organic solvent may be added to the mixture to perform wet pulverization. A predetermined amount of organic solvent may be added to the pulverizing container all at once at the beginning of pulverization, or a predetermined amount of organic solvent may be added to the pulverizing container intermittently in multiple times during the pulverization process. The organic solvent plays a role in preventing the pulverized object from adhering to the inner wall of the pulverizing container.

[0156] As the organic solvent, alcohol, ether, fatty acid, alkane, cycloalkane, silicate, metal alkoxide or the like can be used.

[0157] The raw silicon may be coarse silicon particles having an average particle size of several μm to several tens of μm. The crystallite size of the silicon particles finally obtained, calculated by the Scherrer equation from the half-value width of the diffraction peak attributable to the Si (111) plane in the X-ray diffraction pattern, is preferably controlled to be greater than 5 nm and less than 50 nm.

[0158] It should be noted that the raw silicon and lithium silicate may be micronized and then mixed. In addition, silicon nanoparticles and amorphous lithium silicate nanoparticles may be prepared without using a pulverizing device and then mixed. The nanoparticles may be prepared using a known method such as a gas phase method (e.g., a plasma method) or a liquid phase method (e.g., a liquid phase reduction method).

[0159] Process (c)

[0160] Next, the crushed material is sintered while applying pressure by hot pressing or the like to obtain a sintered body. Firing is performed, for example, in an inert atmosphere (for example, an atmosphere such as argon or nitrogen). The sintering temperature is preferably above 450°C and below 1000°C. If it is within the above temperature range, it is easy to disperse tiny silicon particles in the silicate phase with low crystallinity. During sintering, lithium silicate softens and flows as if filling the gaps between silicon particles. As a result, a dense block-shaped sintered body with a silicate phase as a sea and silicon particles as an island can be obtained. The sintering temperature is preferably above 550°C and below 900°C, and more preferably above 650°C and below 850°C. The sintering time is, for example, above 1 hour and below 10 hours.

[0161] When the obtained sintered body is pulverized, silicate composite particles can be obtained. By appropriately selecting the pulverization conditions, silicate composite particles having a predetermined average particle size can be obtained.

[0162] Through the steps (i) and (ii), composite particles having a silicate phase as a matrix and a silicon phase dispersed in the matrix can be obtained.

[0163] The composite particles may also be composite particles including a silicon oxide phase and a silicon phase dispersed in the silicon oxide phase (composite particles containing a silicon oxide phase). The composite particles containing a silicon oxide phase are composed of, for example, SiO x The composite particles containing a silicon oxide phase are obtained, for example, by heat-treating silicon monoxide to separate it into a silicon oxide phase and a fine silicon phase by a disproportionation reaction.

[0164] The composite particles may also be composite particles including a carbon phase and a silicon phase dispersed in the carbon phase (composite particles containing a carbon phase). The composite particles containing a carbon phase are obtained, for example, by pulverizing a mixture of a carbon source and raw silicon while stirring it with a ball mill or the like to form microparticles, then heat-treating the mixture in an inert atmosphere, and pulverizing the sintered product obtained by the heat treatment. Examples of the carbon source include sugars such as carboxymethyl cellulose (CMC), water-soluble resins such as polyvinyl pyrrolidone, petroleum asphalt, coal asphalt, and the like.

[0165] The carbon phase has electrical conductivity, so in the composite particles containing the carbon phase, even if pores are formed around the composite particles, the contact points between the composite particles and their surroundings are easily maintained. As a result, it is easy to suppress the reduction in capacity caused by repeated charge and discharge cycles. The carbon phase can be composed of amorphous carbon (i.e., non-crystalline carbon). Amorphous carbon can be hard carbon, soft carbon, or anything else. Amorphous carbon (non-crystalline carbon) generally refers to a carbon material having an average interplanar spacing d002 of the (002) plane measured by X-ray diffraction method exceeding 0.34nm.

[0166] From the viewpoint of increasing capacity and improving cycle characteristics, the content of the silicon phase in the composite particles containing the carbon phase may be 30 mass % to 80 mass % or 40 mass % to 70 mass %.

[0167] The average particle size of the composite particles is, for example, not less than 1 μm and not more than 25 μm, or not less than 4 μm and not more than 15 μm. If it is within the above range, good battery performance is easily obtained. It should be noted that, in this specification, the average particle size refers to: the particle size (volume average particle size) at which the volume cumulative value becomes 50% in the particle size distribution measured by the laser diffraction scattering method. The measuring device can be, for example, "LA-750" manufactured by HORIBA Co., Ltd. Among them, the average particle size of the silicon phase dispersed in the ion conductive phase of the composite particles can be calculated using the above method.

[0168] Figure 1 Schematically shows a cross section of the negative electrode material 20 .

[0169] The negative electrode material 20 includes a composite particle 23 (mother particle) and a covering layer 26 covering the surface of the composite particle 23. The composite particle 23 includes an ion conductive phase 21 and a silicon phase (silicon particle) 22 dispersed in the ion conductive phase 21. The composite particle 23 has a sea island structure in which fine silicon phases 22 are dispersed in the matrix of the ion conductive phase 21. The covering layer 26 contains a phosphate compound and a hydrophobic polymer compound. In addition to the composite particles and the covering layer, the negative electrode material may also include other elements. For example, a conductive layer may be sandwiched between the composite particles and the covering layer.

[0170] (Secondary battery)

[0171] The secondary battery of the embodiment of the present disclosure includes a positive electrode, a negative electrode, and an electrolyte. The negative electrode includes the negative electrode material for the secondary battery described above. The negative electrode of the secondary battery and the like are described below.

[0172] [negative electrode]

[0173] The negative electrode contains a negative electrode active material that can absorb and release lithium ions. The negative electrode active material contains the above-mentioned negative electrode material. The negative electrode material contains silicon-containing particles. The average particle size of the silicon-containing particles is, for example, greater than 1 μm and less than 25 μm. From the viewpoint of high capacity and improved cycle characteristics, the silicon-containing particles preferably contain the above-mentioned composite particles. The silicon-containing particles can also be particles of silicon alone or a silicon alloy. The alloy containing silicon, for example, contains silicon (Si) and at least one element selected from the group consisting of tin (Sn), nickel (Ni), iron (Fe), copper (Cu), titanium (Ti), manganese (Mn) and aluminum (Al).

[0174] The negative electrode active material may further contain other active material materials. As other active material materials, for example, carbon-based active materials are preferred. The composite particles expand and shrink in volume with charge and discharge. Therefore, if the ratio of the composite particles in the negative electrode active material increases, poor contact between the negative electrode active material and the negative electrode collector is likely to occur with charge and discharge. On the other hand, by combining the composite particles and the carbon-based active material, while being able to impart a high capacity of the silicon phase to the negative electrode, excellent cycle characteristics can also be achieved. The proportion of the composite particles in the total of the composite particles and the carbon-based active material can be, for example, 0.5 to 15% by mass, or 1 to 10% by mass. As a result, it is easy to take into account both high capacity and improved cycle characteristics.

[0175] As carbon-based active materials, for example, graphite, easily graphitized carbon (soft carbon), and difficultly graphitized carbon (hard carbon) can be exemplified. Among them, graphite having excellent charge and discharge stability and low irreversible capacity is preferred. Graphite refers to a material having a graphite-type crystal structure, for example, including natural graphite, artificial graphite, and graphitized mesophase carbon particles. One carbon-based active material can be used alone, or two or more can be used in combination.

[0176] The negative electrode, for example, comprises a negative electrode current collector and a negative electrode mixture layer supported on the surface of the negative electrode current collector. The negative electrode mixture layer can be formed by applying a negative electrode slurry formed by dispersing a negative electrode mixture in a dispersion medium to the surface of the negative electrode current collector and drying it. The dried coating film can be rolled as needed. The negative electrode mixture layer can be formed on one surface of the negative electrode current collector or on both surfaces.

[0177] The negative electrode mixture contains a negative electrode active material (the negative electrode material described above) as an essential component, and may contain a binder, a conductive agent, a thickener, etc. as optional components.

[0178] As the negative electrode current collector, a nonporous conductive substrate (metal foil, etc.) or a porous conductive substrate (mesh, porous body, punched sheet, etc.) is used. As the material of the negative electrode current collector, stainless steel, nickel, nickel alloy, copper, copper alloy, etc. can be exemplified. The thickness of the negative electrode current collector is not particularly limited, but from the perspective of balancing the strength and lightness of the negative electrode, it is preferably 1 to 50 μm, and more preferably 5 to 20 μm.

[0179] Examples of binders include fluororesins, polyolefin resins, polyamide resins, polyimide resins, vinyl resins, styrene-butadiene rubber (SBR), polyacrylic acid and its derivatives. These can be used alone or in combination of two or more. As conductive agents, examples include carbon black, conductive fibers, carbon fluoride, organic conductive materials, etc. These can be used alone or in combination of two or more. As thickeners, examples include carboxymethyl cellulose (CMC), polyvinyl alcohol, etc. These can be used alone or in combination of two or more.

[0180] Examples of the dispersion medium include water, alcohol, ether, N-methyl-2-pyrrolidone (NMP), and mixed solvents thereof.

[0181] [positive electrode]

[0182] The positive electrode contains a positive electrode active material that can absorb and release lithium ions. For example, a lithium transition metal composite oxide can be used as the positive electrode active material. Examples of lithium transition metal composite oxides include Li a CoO2、Li a NiO2、Li a MnO2、Li a Co b Ni 1-b O2、Li a Co b M 1-b O c , Li a Ni 1-b M b O c , Li a Mn2O4、Li a Mn 2-b M bO4, LiMePO4, Li2MePO4F. Here, M is at least one selected from the group consisting of Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb and B. Me contains at least a transition element (for example, at least one selected from the group consisting of Mn, Fe, Co, and Ni). Here, 0≤a≤1.2, 0≤b≤0.9, and 2.0≤c≤2.3. It should be noted that the value a representing the molar ratio of lithium increases or decreases according to charge and discharge.

[0183] The positive electrode, for example, comprises a positive electrode current collector and a positive electrode mixture layer supported on the surface of the positive electrode current collector. The positive electrode mixture layer can be formed by applying a positive electrode slurry formed by dispersing a positive electrode mixture in a dispersion medium to the surface of the positive electrode current collector and drying it. The dried coating film can be rolled as needed. The positive electrode mixture layer can be formed on one surface of the positive electrode current collector or on both surfaces.

[0184] The positive electrode mixture contains a positive electrode active material as an essential component, and may contain a binder, a conductive agent, etc. as optional components.

[0185] As the binder and the conductive agent, the same substances as those exemplified in the negative electrode can be used. As the conductive agent, graphite such as natural graphite and artificial graphite can be used.

[0186] The shape and thickness of the positive electrode current collector can be selected from the shape and range of the negative electrode current collector. Examples of the material of the positive electrode current collector include stainless steel, aluminum, aluminum alloy, and titanium.

[0187] [Electrolytes]

[0188] The electrolyte has lithium ion conductivity and may be a liquid electrolyte (electrolyte) or a solid electrolyte.

[0189] As a solid electrolyte, for example, a solid or gel-like polymer electrolyte, an inorganic solid electrolyte, etc. can be used. As an inorganic solid electrolyte, a well-known material in an all-solid-state lithium-ion secondary battery, etc. (for example, an oxide-based solid electrolyte, a sulfide-based solid electrolyte, a halogen-based solid electrolyte, etc.) can be used. The polymer electrolyte, for example, comprises a lithium salt and a matrix polymer, or comprises a non-aqueous solvent, a lithium salt, and a matrix polymer. As a matrix polymer, for example, a polymer material that absorbs a non-aqueous solvent and gels is used. As a polymer material, fluororesins, acrylic resins, polyether resins, etc. can be listed.

[0190] The electrolyte solution contains a solvent and an electrolyte salt. As the solvent, a non-aqueous solvent or water may be used. In the case of a lithium ion secondary battery, the electrolyte salt contains at least a lithium salt.

[0191] The concentration of the lithium salt in the electrolyte is preferably, for example, 0.5 mol / L or more and 2 mol / L or less. By controlling the lithium salt concentration within the above range, the ion conductivity is excellent and an electrolyte having a moderate viscosity can be obtained. However, the lithium salt concentration is not limited to the above.

[0192] As the non-aqueous solvent, for example, cyclic carbonates, chain carbonates, cyclic carboxylic acid esters, etc. are used. As cyclic carbonates, propylene carbonate (PC), ethylene carbonate (EC), etc. can be listed. As chain carbonates, diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), etc. can be listed. As cyclic carboxylic acid esters, γ-butyrolactone (GBL), γ-valerolactone (GVL), etc. can be listed. The non-aqueous solvent can be used alone or in combination of two or more.

[0193] As the lithium salt, for example, a lithium salt containing chloric acid (LiClO4, LiAlCl4, LiB 10 Cl 10 etc.), lithium salts of fluorinated acids (LiPF6, LiBF4, LiSbF6, LiAsF6, LiCF3SO3, LiCF3CO2, etc.), lithium salts of fluorinated imides (LiN(CF3SO2)2, LiN(CF3SO2)(C4F9SO2), LiN(C2F5SO2)2, etc.), lithium halides (LiCl, LiBr, LiI, etc.), etc. The lithium salts may be used alone or in combination of two or more.

[0194] [Separator]

[0195] It is usually desirable to sandwich a separator between the positive electrode and the negative electrode. The separator has high ion permeability and has appropriate mechanical strength and insulation. As the separator, a microporous film, a woven fabric, a nonwoven fabric, etc. can be used. As the material of the separator, for example, polyolefins such as polypropylene and polyethylene can be used.

[0196] As an example of the structure of a secondary battery, an electrode group in which the positive electrode and the negative electrode are wound with a separator and an electrolyte are contained in an outer shell can be cited. Alternatively, instead of a wound electrode group, an electrode group in other forms such as a laminated electrode group in which the positive electrode and the negative electrode are laminated with a separator can be applied. The secondary battery can be, for example, in any form such as a cylindrical, square, coin-shaped, button-shaped, laminated, etc.

[0197] Below, refer to Figure 2 The structure of a rectangular secondary battery as an example of the secondary battery of the present disclosure will be described. Figure 2 This is a schematic perspective view in which a portion of a secondary battery according to an embodiment of the present disclosure is cut away.

[0198] The battery includes a square-bottomed battery case 4, and an electrode group 1 and an electrolyte (not shown) housed in the battery case 4. The electrode group 1 includes a long strip-shaped negative electrode, a long strip-shaped positive electrode, and a separator sandwiched between them to prevent direct contact. The electrode group 1 is formed by winding the negative electrode, the positive electrode, and the separator around a flat winding core and removing the winding core.

[0199] One end of the negative electrode lead 3 is mounted on the negative electrode collector by welding or the like. The other end of the negative electrode lead 3 is electrically connected to the negative terminal 6 provided on the sealing plate 5 through a resin insulating plate (not shown). The negative terminal 6 is insulated from the sealing plate 5 by a resin gasket 7. One end of the positive electrode lead 2 is mounted on the positive electrode collector by welding or the like. The other end of the positive electrode lead 2 is connected to the back of the sealing plate 5 through an insulating plate. That is, the positive electrode lead 2 is electrically connected to the battery case 4 which also serves as the positive terminal. The insulating plate separates the electrode group 1 from the sealing plate 5, and also separates the negative electrode lead 3 from the battery case 4. The periphery of the sealing plate 5 is fitted with the opening end of the battery case 4, and the fitting portion is laser welded. In this way, the opening of the battery case 4 is sealed by the sealing plate 5. The injection hole for the electrolyte provided on the sealing plate 5 is blocked by the sealing plug 8.

[0200] "appendix"

[0201] The following techniques are disclosed through the description of the above embodiments.

[0202] (Technology 1)

[0203] A negative electrode material for a secondary battery, comprising silicon-containing particles and a covering layer covering at least a portion of the surface of the silicon-containing particles.

[0204] The aforementioned covering layer contains a phosphate compound and a hydrophobic polymer compound.

[0205] (Technique 2)

[0206] In the negative electrode material for a secondary battery according to technology 1, the silicon-containing particles include composite particles including an ion conductive phase and a silicon phase dispersed in the ion conductive phase.

[0207] (Technique 3)

[0208] In the negative electrode material for a secondary battery according to technology 2, the ion conductive phase includes at least one selected from the group consisting of a silicate phase, a silicon oxide phase, and a carbon phase.

[0209] (Technique 4)

[0210] A negative electrode material for a secondary battery according to any one of technologies 1 to 3, wherein the aforementioned phosphate compound contains at least one phosphate compound selected from the group consisting of phosphate compounds, polyphosphate compounds and metaphosphate compounds containing anions represented by the above-mentioned general formula (1), wherein A is an organic group or an oxygen atom.

[0211] (Technique 5)

[0212] In the negative electrode material for a secondary battery according to the fourth aspect, the organic group is represented by the above-mentioned formula (2).

[0213] (Technique 6)

[0214] The negative electrode material for a secondary battery according to the fourth or fifth aspect, wherein the polyphosphate compound includes at least one selected from the group consisting of tripolyphosphates and tetrapolyphosphates.

[0215] (Technique 7)

[0216] The negative electrode material for a secondary battery according to any one of techniques 4 to 6, wherein the metaphosphate compound includes at least one selected from the group consisting of trimetaphosphates and hexametaphosphates.

[0217] (Technology 8)

[0218] A negative electrode material for a secondary battery according to any one of technologies 4 to 7, wherein the phosphate compound comprises at least one selected from the group consisting of sodium tripolyphosphate, sodium tetrapolyphosphate, sodium trimetaphosphate, sodium hexametaphosphate, potassium trimetaphosphate, potassium hexametaphosphate, disodium etidronate, tetrasodium etidronate, sodium pyrophosphate, potassium pyrophosphate, calcium pyrophosphate and ferric pyrophosphate.

[0219] (Technique 9)

[0220] The negative electrode material for a secondary battery according to any one of technologies 1 to 3, wherein the phosphate compound comprises at least one selected from the group consisting of sodium dihydrogen phosphate, disodium hydrogen phosphate, trisodium phosphate, potassium dihydrogen phosphate, dipotassium hydrogen phosphate, tripotassium phosphate, trilithium phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, triammonium phosphate, calcium dihydrogen phosphate, dicalcium hydrogen phosphate, tricalcium phosphate, magnesium dihydrogen phosphate, dimagnesium hydrogen phosphate, trimagnesium phosphate, aluminum dihydrogen phosphate, aluminum dihydrogen phosphate, trialuminum phosphate, manganese dihydrogen phosphate, zinc phosphate and boron phosphate.

[0221] (Technology 10)

[0222] The negative electrode material for a secondary battery according to any one of techniques 1 to 9, wherein the amount of the phosphate compound attached to the surface of the silicon-containing particles is 1 part by mass or more relative to 100 parts by mass of the silicon-containing particles.

[0223] (Technology 11)

[0224] The negative electrode material for a secondary battery according to any one of techniques 1 to 10, wherein the hydrophobic polymer compound contains a fluororesin.

[0225] (Technology 12)

[0226] The negative electrode material for a secondary battery according to technology 11, wherein the fluororesin comprises at least one selected from the group consisting of polyvinylidene fluoride, polytetrafluoroethylene, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, tetrafluoroethylene-ethylene copolymer, trifluorochloroethylene-ethylene copolymer and polytrifluorochloroethylene.

[0227] (Technology 13)

[0228] The negative electrode material for a secondary battery according to any one of techniques 1 to 12, wherein the amount of the hydrophobic polymer compound attached to the surface of the silicon-containing particles is 1 part by mass or more relative to 100 parts by mass of the silicon-containing particles.

[0229] (Technology 14)

[0230] The secondary battery negative electrode material according to any one of techniques 1 to 13, wherein ions derived from the phosphate compound are detected in the coating layer by time-of-flight secondary ion mass spectrometry.

[0231] (Technology 15)

[0232] The negative electrode material for a secondary battery according to the technique 2 or 3, wherein a conductive layer containing a conductive carbon material is interposed between the composite particles and the covering layer.

[0233] (Technology 16)

[0234] A negative electrode material for a secondary battery, comprising silicon-containing particles and a covering layer covering at least a portion of the surface of the silicon-containing particles.

[0235] The aforementioned covering layer contains a phosphate compound and a water-insoluble polymer compound.

[0236] (Technology 17)

[0237] A secondary battery comprising a positive electrode, a negative electrode and an electrolyte.

[0238] The negative electrode includes the negative electrode material for a secondary battery according to any one of Techniques 1 to 16.

[0239] [Example]

[0240] Hereinafter, examples of the present disclosure will be described in detail, but the present disclosure is not limited to the following examples.

[0241] 《Secondary batteries A1~A3》

[0242] (Preparation of composite particles)

[0243] Lithium carbonate (Li2CO3) as a Li raw material and silicon dioxide (SiO2) as a Si raw material are mixed in such a way that the atomic ratio: Si / Li becomes 1.05 to obtain a mixture. The mixture is calcined at 800°C for 10 hours in an inert gas atmosphere to obtain lithium silicate (Li2Si2O5). The obtained lithium silicate is crushed to an average particle size of 10 μm.

[0244] The pulverized lithium silicate and raw silicon (3N, average particle size 10 μm) were mixed at a mass ratio of 40:60. The mixture was filled in a pot (SUS, volume: 500 mL) of a planetary ball mill (Fritsch, P-5). Next, 24 SUS balls (diameter 20 mm) were placed in the pot and the lid was closed, and the mixture was pulverized at 200 rpm for 50 hours in an inert atmosphere.

[0245] Next, the powdered mixture was taken out in an inert atmosphere, and calcined at 600°C for 4 hours under pressure from a hot press in an inert atmosphere to obtain a sintered body of the mixture. The sintered body of the obtained mixture was crushed and passed through a 40 μm mesh to obtain composite particles (composite particles containing a silicate phase). Then, a sieve was used to obtain composite particles with an average particle size of 10 μm.

[0246] The crystallite size of the silicon phase is 15 nm. The silicon phase is granular, and the average particle size of the silicon phase is 20 nm. The main component of the silicate phase is Li2Si2O5, and the content of the silicon phase in the composite particles containing the silicate phase is 60 mass%.

[0247] (Formation of Conductive Layer)

[0248] Then, 100 parts by mass of the composite particles were mixed with 3 parts by mass of coal tar pitch, and the mixture was calcined at 800° C. in an inert atmosphere to cover the surface of the composite particles with conductive carbon. In this way, a conductive layer was formed on the surface of the composite particles. The covering amount of the conductive layer was 3% by mass relative to the total of the composite particles and the conductive layer.

[0249] (Manufacturing of negative electrode materials)

[0250] (1st step)

[0251] Pure water was added to the phosphate compound and stirred for 30 minutes, and then, composite particles having a conductive layer were further added and stirred for 30 minutes. Then, the mixture was dried at 80°C for 12 hours to remove water. In this way, a first intermediate (composite particles having a phosphate compound attached to the surface) was obtained. A high-speed stirrer (manufactured by PRIMIX Corporation) was used as the stirring device. The amount of the phosphate compound added was the value shown in Table 1 relative to 100 parts by mass of the composite particles. Disodium etidronate was used as the phosphate compound.

[0252] (Second step)

[0253] PVDF powder was added to the first intermediate and dry mixed to obtain a second intermediate (composite particles with a phosphate compound and PVDF attached to the surface). The amount of PVDF added was the value shown in Table 1 relative to 100 parts by mass of the composite particles. Dry mixing was performed by ball milling at room temperature (25°C) for 30 minutes. The ball milling process used "ROKING MILL" manufactured by Seiwa giken Co., Ltd., using spherical zirconium oxide (diameter 3 mm).

[0254] (Step 3)

[0255] The second intermediate was heat treated at 250°C for 2 hours in an inert atmosphere. The heat treatment liquefied the PVDF attached to the surface of the composite particles, thereby improving the retention of the phosphate compound on the surface of the composite particles. In this way, a coating layer containing the phosphate compound and PVDF was formed on the surface of the composite particles having a conductive layer, thereby obtaining a negative electrode material.

[0256] The TOF-SIMS analysis revealed that ions derived from etidronate disodium were detected on the surface of the negative electrode material, and the XPS analysis confirmed that PVDF was distributed more in the surface layer of the covering layer than in the inner layer of the covering layer.

[0257] (Production of negative electrode)

[0258] Graphite and composite particles (negative electrode material) having a conductive layer and a coating layer were mixed in a mass ratio of 90:10 and used as a negative electrode active material. 1 mass part of carboxymethyl cellulose (CMC) and 1.5 mass parts of styrene-butadiene rubber (SBR) were added to 97.5 mass parts of the negative electrode active material, and a predetermined amount of water was added to prepare a negative electrode slurry.

[0259] The negative electrode slurry is applied to both sides of the copper foil as the negative electrode collector, and the coating is dried, rolled, and then cut into a predetermined size to obtain a negative electrode having a negative electrode mixture layer formed on both sides of the negative electrode collector. At this time, a negative electrode collector exposed portion is provided at a part of the negative electrode.

[0260] (Production of positive electrode)

[0261] 2.5 parts by mass of acetylene black and 2.5 parts by mass of polyvinylidene fluoride were added to 95 parts by mass of the positive electrode active material, and then an appropriate amount of N-methyl-2-pyrrolidone (NMP) was added to prepare a positive electrode slurry. 0.88 Co 0.09 Al 0.03 A lithium transition metal composite oxide represented by O2.

[0262] The positive electrode slurry is applied to both sides of the aluminum foil as the positive electrode collector, the coating is dried, rolled, and then cut into a predetermined size to obtain a positive electrode having positive electrode mixture layers formed on both sides of the positive electrode collector. At this time, a positive electrode collector exposed portion is provided at a part of the positive electrode.

[0263] (Preparation of Electrolyte)

[0264] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) were mixed at a volume ratio of 20:5:75 to obtain a mixed solvent. Lithium hexafluorophosphate was dissolved in the mixed solvent at a concentration of 1 mol / L to prepare an electrolyte solution.

[0265] (Manufacturing of Secondary Batteries)

[0266] An aluminum positive electrode lead is installed on the exposed part of the positive electrode collector of the positive electrode, and a nickel negative electrode lead is installed on the exposed part of the negative electrode collector of the negative electrode. The positive electrode and the negative electrode are spirally wound with a polyolefin separator, and then pressed in the radial direction to produce a flat wound electrode body. The electrode body is housed in an outer shell composed of an aluminum laminate, and after injecting an electrolyte, the opening of the outer shell is sealed. In this way, secondary batteries A1 to A3 for evaluation are obtained.

[0267] 《Secondary Battery B1》

[0268] Secondary battery B1 was obtained in the same manner as secondary battery A1 except that a coating layer was not formed on the surface of the composite particles having a conductive layer.

[0269] 《Secondary batteries B2~B4》

[0270] Secondary batteries B2 to B4 were obtained in the same manner as secondary batteries A1 to A3 except that the second step and the third step were not performed and PVDF was not added.

[0271] 《Secondary Battery B5》

[0272] Secondary battery B5 was obtained in the same manner as secondary battery A1 except that the first step was not performed and the phosphate compound was not added.

[0273] [evaluate]

[0274] The secondary batteries A1 to A3 and B1 to B5 obtained above were evaluated as follows.

[0275] (Cycle degradation rate)

[0276] In an environment of 25°C, constant current charging was performed at a current of 0.3C until the voltage reached 4.2V, and then constant voltage charging was performed at a voltage of 4.2V until the current reached 0.02C. Then, discharge was performed at a current of 0.5C until the voltage reached 2.5V. This charge and discharge was regarded as one cycle, and 300 cycles were performed.

[0277] The discharge capacity retention rate R (%) was calculated from the following formula using the discharge capacity C1 at the first cycle and the discharge capacity C2 at the 300th cycle.

[0278] Discharge capacity retention rate R = (discharge capacity C2 / discharge capacity C1) × 100

[0279] The obtained discharge capacity retention rate R was used to determine the cycle degradation rate at 300 cycles according to the following formula: It should be noted that R0 in the formula is the discharge capacity retention rate R of the secondary battery B1.

[0280] Cycle degradation rate = {(100-R) / (100-R0)}×100

[0281] The evaluation results are shown in Table 1. In Table 1, A1 to A3 are batteries of Examples, and B1 to B5 are batteries of Comparative Examples.

[0282] [Table 1]

[0283]

[0284] Batteries A1 to A3 had smaller cycle degradation rates than batteries B1 to B5, and thus achieved excellent cycle characteristics.

[0285] When the phosphate compound was added, the cycle degradation rate was significantly reduced by the addition of PVDF compared to the case where the phosphate compound was not added (B1→B5, B2→A1, B3→A2, B4→A3).

[0286] 《Secondary batteries C1~C3 and D1~D5》

[0287] Composite particles containing a carbon phase are used as the composite particles. Composite particles containing a carbon phase are prepared as follows.

[0288] Coal tar pitch (MCP250 manufactured by JFE Chemical Corporation) as a carbon source and raw silicon (3N, average particle size 10 μm) were mixed at a mass ratio of 50:50. The mixture was filled into a pot (SUS, volume: 500 mL) of a planetary ball mill (P-5 manufactured by Fritsch), 24 SUS balls (diameter 20 mm) were placed in the pot and the lid was closed, and the mixture was pulverized at 200 rpm for 50 hours in an inert atmosphere to obtain a composite of silicon phase and carbon source.

[0289] Next, the composite of the silicon phase and the carbon source is sintered in an inert gas atmosphere to carbonize the carbon source, thereby obtaining a sintered product in which the silicon phase is dispersed in the carbon phase containing amorphous carbon. The sintered product is then pulverized using a jet mill to obtain composite particles containing the carbon phase with an average particle size of 10 μm.

[0290] The crystallite size of the silicon phase was 15 nm. The silicon phase was in a granular form, and the average particle size of the silicon phase was 20 nm. The content of the silicon phase in the composite particles containing the carbon phase was 60 mass %.

[0291] No conductive layer was formed on the surface of the composite particles containing the carbon phase. In the manufacturing process of the negative electrode material, the composite particles containing the carbon phase were used instead of the composite particles containing the silicate phase having the conductive layer, and the secondary batteries C1 to C3 were obtained in the same manner as the secondary batteries A1 to A3. In addition, in addition to the above, the secondary batteries D1 to D5 were obtained in the same manner as the secondary batteries B1 to B5.

[0292] The secondary batteries C1 to C3 and D1 to D5 obtained above were evaluated in the same manner as above to determine the cycle degradation rate at 350 cycles. C2 of the formula for the discharge capacity retention rate R is the 350th cycle discharge capacity. R0 of the formula for the cycle degradation rate is the discharge capacity retention rate R of the secondary battery D1.

[0293] The evaluation results are shown in Table 2. In Table 2, C1 to C3 are batteries of Examples, and D1 to D5 are batteries of Comparative Examples.

[0294] [Table 2]

[0295]

[0296] Batteries C1 to C3 had smaller cycle degradation rates than batteries D1 to D5, and thus achieved excellent cycle characteristics.

[0297] In the case where the phosphate compound was added, the cycle degradation rate was significantly reduced by the addition of PVDF compared to the case where the phosphate compound was not added (D1→D5, D2→C1, D3→C2, D4→C3).

[0298] 《Secondary batteries E1 and F1~F3》

[0299] As silicon-containing particles, Si single-substance particles (average particle size 10 μm) were used instead of composite particles. No conductive layer was formed on the surface of the Si single-substance particles. In the manufacturing process of the negative electrode material, Si single-substance particles were used instead of composite particles containing a silicate phase having a conductive layer. Secondary battery E1 was obtained in the same manner as secondary battery A2. In addition, in addition to the above, secondary batteries F1 to F2 were obtained in the same manner as secondary batteries B1, B3, and B5, respectively.

[0300] The secondary batteries E1, F1 to F3 obtained above were evaluated in the same manner as above to determine the cycle degradation rate at 100 cycles. C2 of the calculation formula for the discharge capacity retention rate R is the discharge capacity at the 100th cycle. R0 of the calculation formula for the cycle degradation rate is the discharge capacity retention rate R of the secondary battery F1.

[0301] The evaluation results are shown in Table 3. In Table 3, E1 is a battery of an example, and F1 to F3 are batteries of comparative examples.

[0302] [Table 3]

[0303]

[0304] Battery E1 had a smaller cycle degradation rate than batteries F1 to F3, and obtained excellent cycle characteristics.

[0305] When the phosphate compound was added, the cycle degradation rate was significantly reduced by the addition of PVDF compared to the case where the phosphate compound was not added (F1→F3, F2→E1).

[0306] Industrial Applicability

[0307] The secondary battery of the present disclosure is useful as a main power source for mobile communication devices, portable electronic devices, and the like.

[0308] The present invention has been described with respect to the presently preferred embodiments, but such disclosure is not to be construed in a limiting sense. Various modifications and changes should be apparent to those skilled in the art in the art of the present invention upon reading the above disclosure. Therefore, the appended claims should be construed as including all modifications and changes without departing from the spirit and scope of the present invention.

[0309] Description of Reference Numerals

[0310] 1: electrode group, 2: positive electrode lead, 3: negative electrode lead, 4: battery casing, 5: sealing plate, 6: negative electrode terminal, 7: gasket, 8: sealing plug, 20: negative electrode material, 21: ion conductive phase, 22: silicon phase, 23: composite particles, 26: covering layer.

Claims

1. A negative electrode material for a secondary battery, comprising silicon-containing particles and a covering layer covering at least a portion of the surface of the silicon-containing particles, The cover layer includes a phosphate compound and a hydrophobic polymer compound.

2. The negative electrode material for a secondary battery according to claim 1, wherein The silicon-containing particles include composite particles including an ion-conducting phase and a silicon phase dispersed in the ion-conducting phase.

3. The negative electrode material for a secondary battery according to claim 2, wherein: The ion conductive phase includes at least one selected from the group consisting of a silicate phase, a silicon oxide phase, and a carbon phase.

4. The negative electrode material for a secondary battery according to claim 1, wherein The phosphate compound comprises at least one phosphate compound selected from the group consisting of a phosphate compound containing an anion represented by the general formula (1), a polyphosphate compound, and a metaphosphate compound, In the general formula (1), A is an organic group or an oxygen atom.

5. The negative electrode material for a secondary battery according to claim 4, wherein The organic group is represented by formula (2), 6. The negative electrode material for a secondary battery according to claim 4, wherein The polyphosphate compound includes at least one selected from the group consisting of tripolyphosphates and tetrapolyphosphates.

7. The negative electrode material for a secondary battery according to claim 4, wherein The metaphosphate compound includes at least one selected from the group consisting of trimetaphosphate and hexametaphosphate.

8. The negative electrode material for a secondary battery according to claim 4, wherein The phosphate compound includes at least one selected from the group consisting of sodium tripolyphosphate, sodium tetrapolyphosphate, sodium trimetaphosphate, sodium hexametaphosphate, potassium trimetaphosphate, potassium hexametaphosphate, disodium etidronate, tetrasodium etidronate, sodium pyrophosphate, potassium pyrophosphate, calcium pyrophosphate, and ferric pyrophosphate.

9. The negative electrode material for a secondary battery according to claim 1, wherein The phosphate compound includes at least one selected from the group consisting of sodium dihydrogen phosphate, disodium hydrogen phosphate, trisodium phosphate, potassium dihydrogen phosphate, dipotassium hydrogen phosphate, tripotassium phosphate, trilithium phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, triammonium phosphate, calcium dihydrogen phosphate, dicalcium hydrogen phosphate, tricalcium phosphate, magnesium dihydrogen phosphate, dimagnesium hydrogen phosphate, trimagnesium phosphate, aluminum dihydrogen phosphate, aluminum dihydrogen phosphate, trialuminum phosphate, manganese dihydrogen phosphate, zinc phosphate and boron phosphate.

10. The negative electrode material for a secondary battery according to claim 1, wherein The amount of the phosphate compound attached to the surface of the silicon-containing particles is 1 part by mass or more relative to 100 parts by mass of the silicon-containing particles.

11. The negative electrode material for a secondary battery according to claim 1, wherein The hydrophobic polymer compound includes a fluororesin.

12. The negative electrode material for a secondary battery according to claim 11, wherein The fluororesin includes at least one selected from the group consisting of polyvinylidene fluoride, polytetrafluoroethylene, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, tetrafluoroethylene-ethylene copolymer, chlorotrifluoroethylene-ethylene copolymer and polychlorotrifluoroethylene.

13. The negative electrode material for a secondary battery according to claim 1, wherein The amount of the hydrophobic polymer compound attached to the surface of the silicon-containing particles is 1 part by mass or more relative to 100 parts by mass of the silicon-containing particles.

14. The negative electrode material for a secondary battery according to claim 1, wherein By time-of-flight secondary ion mass spectrometry, ions derived from the phosphate compound were detected in the cover layer.

15. The negative electrode material for a secondary battery according to claim 2, wherein: A conductive layer containing a conductive carbon material is interposed between the composite particles and the covering layer.

16. A negative electrode material for a secondary battery, comprising silicon-containing particles and a covering layer covering at least a portion of the surface of the silicon-containing particles, The covering layer contains a phosphate compound and a water-insoluble polymer compound.

17. A secondary battery comprising a positive electrode, a negative electrode and an electrolyte, The negative electrode comprises the negative electrode material for a secondary battery according to claim 1 .

Citation Information

Patent Citations

  • Negative electrode active substance for secondary battery, and secondary battery

    WO2019151016A1

  • Negative electrode active material for secondary cell, and secondary cell

    WO2019151026A1